2016
DOI: 10.2903/j.efsa.2016.4578
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the health status of managed honeybee colonies (HEALTHY-B): a toolbox to facilitate harmonised data collection

Abstract: Tools are provided to assess the health status of managed honeybee colonies by facilitating further harmonisation of data collection and reporting, design of field surveys across the European Union (EU) and analysis of data on bee health. The toolbox is based on characteristics of a healthy managed honeybee colony: an adequate size, demographic structure and behaviour; an adequate production of bee products (both in relation to the annual life cycle of the colony and the geographical location); and provision o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 451 publications
(309 reference statements)
0
16
0
Order By: Relevance
“…Pesticide toxicity is amplified by multiple interacting stressors [5,20] and thus a holistic approach that tests more of the different conditions that bees naturally experience is beneficial [39,75]. Although sensitivity to pesticides is influenced by season, bee type and concomitant pesticide exposure [44,76], current RA schemes implement only limited tests, requiring only the evaluation of single pesticide effects on in-hive summer bees [77].…”
Section: Discussionmentioning
confidence: 99%
“…Pesticide toxicity is amplified by multiple interacting stressors [5,20] and thus a holistic approach that tests more of the different conditions that bees naturally experience is beneficial [39,75]. Although sensitivity to pesticides is influenced by season, bee type and concomitant pesticide exposure [44,76], current RA schemes implement only limited tests, requiring only the evaluation of single pesticide effects on in-hive summer bees [77].…”
Section: Discussionmentioning
confidence: 99%
“…A measure of population growth was calculated by determining the percent rate of change from the first sample to the second sample of both sealed brood and workers. Previous studies have found that colony strength and its rate of change is a reliable measure of colony health [27]. The formula we used to estimate the percentage rate of colony population change between the first and second samplings of the colonies is described below.…”
Section: Study Site and Colony Health Measuresmentioning
confidence: 99%
“…According to previous studies and current definitions used in regulatory documents (Chauzat et al, 2013;EFSA, 2016;EFSA AHAW Panel, 2016;Jacques et al, 2016), the beekeeper category assessment is based on the level of income generated by beekeeping (i.e. whether the activity generates a "significant source of income").…”
Section: Covariatesmentioning
confidence: 99%
“…Beekeeping Management Practices (BMPs) represent the actions implemented by a beekeeper (according to season, legislation, geographic area, cultural background etc.) to maintain healthy honey bee colonies and to achieve his/her agricultural and food production objectives (Ritter and Akratanakul, 2006;EFSA AHAW Panel, 2016). Several national and European monitoring projects, such as APENET (Porrini et al, 2016), the German Bee Monitoring Project (Genersch et al, 2010), EPILOBEE (Laurent et al, 2015;Chauzat et al, 2016) and COLOSS (Gray et al, 2019) highlighted the direct and/or indirect role of the beekeeper in preserving the health and ensuring the productivity of honey bee colonies.…”
Section: Introductionmentioning
confidence: 99%